Analisis Strategi Penerapan Sumber Dana Pada Produk Pembiayaan Dana Talangan Haji Di Bank Sumut Syariah KC Sibolga - Melisa Lubis; Nursantri Yanti; Nurul Jannah (UNIVED Press, 2023)
This research aims to analyze the application of funding sources to Hajj bailout financing products at Bank Sumut Syariah KC Sibolga. The research method applied is descriptive qualitative with a case study approach. Data was collected through in-depth interviews with bank employees in the finance department, as well as through the study of related documents. This SWOT analysis shows that Bank Sumut Syariah KC Sibolga has various strengths that can be utilized to increase the application of funding sources in Hajj bailout financing products. However, they also face several weaknesses and threats that need to be managed with effective strategies. By taking advantage of existing opportunities and overcoming the challenges faced, banks can optimize this product to meet the needs of prospective Hajj pilgrims and strengthen their position in the market. To ensure the availability of funding sources for Hajj bailout financing products, Bank Sumut Syariah KC Sibolga must take advantage of existing strengths and opportunities with an effective strategy. Managing internal weaknesses, such as limited funding sources and process complexity, as well as mitigating external threats, including regulatory changes and intense competition, will be the key to success. A good strategy will include innovative product development, increased education and outreach, as well as partnership strategies to expand product reach and effectiveness.